3D Rotation‐Trackable and Differentiable Micromachines with Dimer‐Type Structures for Dynamic Bioanalysis. (16th November 2020) - Lin, Gungun; Liu, Yuan; Huang, Guan; Chen, Yinghui; Makarov, Denys; Lin, Jun; Quan, Zewei; Jin, Dayong
Abstract : Utilizing the magnetic interactions between microparticle building blocks allows creating long‐range ordered structures and constructing smart multifunctional systems at different scales. The elaborate control over the inter‐particle magnetic coupling interaction is entailed to unlock new magnetoactuation functionalities. Herein, dimer‐type microstructures consisting of a pair of magnetic emulsions with tailorable dimension and magnetic coupling strength are fabricated using a microfluidic emulsion‐templated assembly approach. The magnetite nanoparticles dispersed in vinylbenzene monomers are partitioned into a pair of emulsions with conserved volume, which are wrapped by an aqueous hydrogel shell and finally polymerized to form discrete structures. Tunable synchronous–asynchronous rotation over 60 dB is unlocked in magnetic dimers, which is shown to be dependent on the magnetic moments induced. This leads to a new class of magnetic actuators for the parallelized assay of distinctive virus DNAs and the dynamic optical evaluation of 3D cell cultures. The work suggests a new perspective to design smart multifunctional microstructures and devices by exploring their natural variance in magnetic coupling. Abstract : Micromachines consisting of tailorable microcompartments are synthesised by a novel emulsion fission approach that is devised to precisely allocate the magnetic content in between the compartments of the dimer structures. This unlocks a couple of new degrees of freedom to engineer magnetic coupling in discrete magnetic structure assemblies and uncovers a series of multifunctional micro‐actuators for complex and dynamic bioanalysis.